HIV-1-Transmitted Drug Resistance and Transmission Clusters in Newly Diagnosed Patients in Portugal Between 2014 and 2019 - Pingarilho, Marta; Pimentel, Victor; Miranda, Mafalda N. S.; Silva, Ana Rita; Diniz, António; Ascenção, Bianca Branco; Piñeiro, Carmela; Koch, Carmo; Rodrigues, Catarina; Caldas, Cátia; Morais, Célia; Faria, Domitília; et al. (Frontiers in Microbiology, 2022)
Objective: To describe and analyze Transmitted Drug Resistance (TDR) between 2014 and 2019 in newly infected HIV-1 patients in Portugal and to characterize its transmission networks. Methods: Clinical, socio-epidemiological and risk behavior data was collected from 820 newly diagnosed patients in Portugal between September 2014 and December 2019. Sequences obtained from drug resistance testing were used for subtyping, TDR determination and transmission clusters (TC) analyses. Results: In Portugal, the overall prevalence of TDR between 2014 and 2019 was 11.0%. TDR presented a decreasing trend from 16.7% in 2014 to 9.2% in 2016 (pfor-trend = 0.114). Multivariate analysis indicated that TDR was significantly associated with transmission route (MSM presented lower probability of presenting TDR when compared to heterosexual contact) and with subtype (subtype C presented significantly more TDR when compared to subtype B). TC analysis corroborated that the heterosexual risk group presented a higher proportion of TDR in TCs when compared to MSMs. Among subtype A1, heterosexuals reached 16.6% of TDR, followed by 14.2% in patients infected with subtype B and 9.4% in patients infected with subtype G. Conclusion: Our molecular epidemiology approach indicates that the HIV-1 epidemic in Portugal is changing among risk group populations, with heterosexuals showing increasing levels of HIV-1 transmission and of TDR. Prevention measures for this subpopulation should be reinforced